The pagan kingdoms in the Gulf of Guinea and their role in fighting European colonialism during the 19th century AD (the kingdoms of Dahomey and Ashanti) as a model - oiakrin, Ahlem; bedida, lazhar (The Algerian Historical Journal, 2026)
Since the landing of their first ships in the Gulf of Guinea, France and Britain have worked to establish good relations with the peoples of this region, in order to tighten their grip and commercial and political control, which made the two European countries enter into a conflict that in many cases could turn into a bloody conflict had it not been for the Diplomacy intervened in the terminology of the conflict between the two parties. France and Britain, during their attempt to penetrate into the interior of the Gulf of Guinea region during the last quarter of the 19th century AD, were subjected to fierce and valiant resistance by the local population. The spirit of this resistance was embodied by the Dahomey people and the strong Ashanti people, who rejected all Forms of subordination to the colonizer. The two European countries used various means by recruiting officers and consuls who pursued a peaceful policy by concluding friendship and trade treaties with African leaders at times, and the policy of war by launching military and combing campaigns at other times.